Misinformation About COVID-19 in Sub-Saharan Africa: Evidence from a Cross-Sectional Survey - Osuagwu, Uchechukwu L; Miner, Chundung A; Bhattarai, Dipesh; Mashige, Percy; Oloruntoba, Richard; Abu, Emmanuel; Ekpeyong, Benerdine; Chikasirimobi, Timothy; Piwuna, Christopher; Ovenseri-Ogbomo, Godwin (Mary Ann Liebert, 2021)
Misinformation about coronavirus disease 2019 (COVID-19) is a significant threat to global public health because it can inadvertently exacerbate public health challenges by promoting spread of the disease. This study used a convenience sampling technique to examine factors associated with misinformation about COVID-19 in sub-Saharan Africa using an online cross-sectional survey. A link to the online self-administered questionnaire was distributed to 1,969 participants through social media platforms and the authors' email networks. Four false statements—informed by results from a pilot study—were included in the survey. The participants' responses were classified as “Agree,” “Neutral,” and “Disagree.” A multinomial logistic regression was used to examine associated factors. Among those who responded to the survey, 19.3% believed that COVID-19 was designed to reduce world population, 22.2% thought the ability to hold your breath for 10 seconds meant that you do not have COVID-19, 27.8% believed drinking hot water flushes down the virus, and 13.9% thought that COVID-19 had little effect on Blacks compared with Whites. An average of 33.7% were unsure whether the 4 false statements were true. Multivariate analysis revealed that those who thought COVID-19 was unlikely to continue in their countries reported higher odds of believing in these 4 false statements. Other significant factors associated with belief in misinformation were age (older adults), employment status (unemployed), gender (female), education (bachelor's degree), and knowledge about the main clinical symptoms of COVID-19. Strategies to reduce the spread of false information about COVID-19 and other future pandemics should target these subpopulations, especially those with limited education. This will also enhance compliance with public health measures to reduce spread of further outbreaks.